Penetrasi Testing Aplikasi Website Udacoding - Kushardianto, Nur Cahyono; Sari, Festy Winda; Haikal, Antoni; Idris, Muhammad (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2023)
Abstract"” The rapid advancement of technology, particularly the internet, has propelled humanity into a modern world where digitalization is essential. Consequently, system security has become paramount in the utilization of information systems, including websites and desktop/mobile applications. According to the National Cyber and Crypto Agency (BSSN), Indonesia remains the top target for cyberattacks. Penetration testing is a lawful practice employed to identify vulnerabilities within a system and enhance its overall security. This penetration testing exercise was conducted on the website Udacoding, following a four-phase approach: planning, information gathering, attack simulation, and reporting. The findings and proposed solutions will be comprehensively documented in a final report.